THE IMPACT OF CHATGPT ON THE TRANSLATION INDUSTRY (Ta'limning zamonaviy transformatsiyasi, 2024)
The following article communicates about the impacts of ChatGPT on translation industry, its benefits and drawbacks to translation systems, and the risks of replacing translators with artificial intelligence.